Radio goes to war : the cultural politics of propaganda during World War II - Horten, Gerd, 1959- (University of California Press, 2003)
Radio Goes to War is the first comprehensive and in-depth look at the role of domestic radio in the United States during the Second World War. As this study convincingly demonstrates, radio broadcasting played a crucial role both in government propaganda and within the context of the broader cultural and political transformations of wartime America.